Does Poststroke Lower-Limb Spasticity Influence the Recovery of Standing Balance Control? A 2-Year Multilevel Growth Model. (August 2016) - Singer, Jonathan C.; Nishihara, Kanako; Mochizuki, George
Background . Poststroke lower-limb spasticity (LLS) has been shown to degrade standing balance control by disrupting the temporal synchronization between individual limb centers of pressure (COPs). Time-varying changes in standing balance control associated with alterations in the extent of LLS have yet to be documented and are important to informing treatment strategies to improve such functional outcomes. Objective . The present work aimed to understand the natural recovery of standing balance control among stroke survivors with LLS using limb-specific indices of standing balance control. Furthermore, we sought to understand if time-varying changes in LLS were associated with alterations in standing balance control. Methods . A retrospective analysis of 92 participants was performed; 47 participants never exhibited LLS during the study (No_LLS), and 45 participants exhibited LLS during at least 1 testing session (LLS). Quiet standing for a duration of 30 s on 2 force platforms was recorded. Temporal synchrony and spatial symmetry of COP displacements were assessed, along with interlimb weight-bearing symmetry. Results . All variables, except spatial symmetry, indicated initial improvement followed by deceleration in the rate of balance control recovery. Limb-specific measures indicated that individuals with LLS exhibited deficits in balance control. The recovery trajectories were not different between groups, suggesting a similar rate, but reduced extent, of balance control recovery among the LLS relative to the No_LLS group. Only temporal synchrony was altered by time-varying changes in spasticity. Conclusions . The present results suggest that the reduction in spasticity may be beneficial to balance control recovery.